[OP.7B.06] METABOLIC SYNDROME IN EUROPEAN RURAL POPULATION- DATA FROM THE BRISGHELLA HEART STUDY (ITALY) AND ENAH STUDY (CROATIA). (September 2016) - Parini, A.; Ivkovic, V.; Vrdoljak, A.; Baric, M. Abramovic; Bacchelli, S.; Cagnati, M.; Cicero, A.F.G.; D'addato, S.; Esposti, D. Degli; Fucek, M.; Grandi, E.; Ivandic, E.; et al.
Abstract : Objective: Prevalence and characteristics of metabolic syndrome (MS) differ among various populations worldwide. This might explain the observed divergences in association of MS with cardiovascular (CV) and chronic kidney disease (CKD) outcomes. Our aim was to analyze differences in MS between two rural continental populations from South Europe (Italy and Croatia) and its association with CKD and hypertension (HT). Design and method: In this international prospective long-term follow up study data on 5162 subjects from BrEna cohort formed from original cohorts of Brisighella Heart Study (Italy) and ENAH study (Croatia) were analyzed. Out of them 1839 subjects (796 m, 1043 w) were eligible for further analyses, 848 from Croatian and 991 from Italian cohort. NCEP ATP III definition was used for MS diagnosis, CKD was defined as eGFR < 60 ml/min, and HT as BP > = 140/90 mmHg and/or taking antihypertensive drugs. Results: Overall prevalence of MS in the whole group was 32% without differences between Croatian and Italian subgroups (32.8% vs. 31.4%; p = 0.55). In Croatian group MS was more frequently present in women (35.7% vs. 27.2%; p = 0.01), while this was not found in Italian group (32.8% vs. 30.0%). Significant differences were observed in prevalence of pathological values of fasting blood glucose, triglycerides, HDL-cholesterol, waist circumference and blood pressure (52.2 vs. 40.2; 71.9 vs. 64.3; 34.2 vs. 69.9; 93.2 vs. 72.0; 89.9 vs. 95.8, respectively, all p < 0.05). We failed to observe difference in the number (3, 4 or 5) of diagnostic elements for MS between the two groups (p > 0.05). There was no difference in prevalence of HT (84.9 vs. 86.3%, p = 0.62). However, CKD was significantly more prevalent in Italian cohort (23.5% vs. 20.5%; p = 0.001). HT was significantly more prevalent in MS than in non-MS group, while we failed to find difference in CKD. Conclusions: Although prevalence of MS was the same in two European rural region, significant differences in characteristics of MS were observed between Croatian and Italian subgroups. Observed differences could be explained more with lifestyle and tradition than genetic variations. Characteristics of MS should be separately analyzed in each population and results should be implemented in national programs and strategies for CKD prevention.